UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI METODE KONTEKSTUAL (CONTEXTUAL LEARNING) DI KELAS IV SDN NO. 202 USOR TOLANG KECAMATAN KOTANOPAN - Israwati Israwati (Jurnal Guru Kita PGSD, 2017)
Abstract: Efforts to Improve Student Mathematics Learning Outcomes through Contextual Learning Method In Grade IV SDN No. 202 Usor Tolang Kecamatan Kotanopan. Based on the results of pre-cycle test of 20 students only 6 students (30%) who scored 70 and above (thorough). While the other 14 students (70%) got a score below 70 (not complete). The aim of this research is to know how far the use of the method can improve student learning outcomes in the material understand the Operation of Counting Numbers in Class V SD Negeri. 202 Usor Tolang Kecamatan Kotanopan Mandailing Natal Regency. From the research on the cycle I percentage mastery of students 65% and grade 55.6% completeness score. In the second cycle students' completeness of 100% and grade 87.2% score of mastery. Percentage mastery learning increased 35.0% and grade score of 31.6%. Likewise with student activity on the first cycle of 61.9%, while going on the second cycle of 74.0%. This means there is an increase in student activity from cycle I to cycle II of 12.10%.Keywords : Contextual Learning, Mathematics, Student Activity, Learning Value ResultAbstrak : Upaya Meningkatkan Hasil Belajar Matematika Siswa Melalui Metode Kontekstual (Contextual Learning) Di Kelas IV SDN No. 202 Usor Tolang Kecamatan Kotanopan. Berdasarkan hasil test pra siklus dari 20 siswa hanya 6 siswa (30%) yang memperoleh nilai 70 ke atas (tuntas). Sedangkan 14 siswa yang lain (70%) mendapat nilai dibawah 70 (tidak tuntas). Penelitian bertujuan untuk mengetahui sejauh mana penggunaan metode tersebut dapat meningkatkan hasil belajar siswa pada materi memahami Operasi Hitung Bilangan di Kelas V SD Negeri No. 202 Usor Tolang Kecamatan Kotanopan Kabupaten Mandailing Natal. Dari penelitian pada siklus I presentase ketuntasan belajar siswa 65% dan skor nilai ketuntasan kelas 55,6%. Pada siklus II ketuntasan belajar siswa sebesar 100% dan skor nilai ketuntasan kelas 87,2%. Presentase ketuntasan belajar terjadi peningkatan sebesar 35,0% dan skor nilai ketuntasan kelas sebesar 31,6%. Begitu juga dengan aktivitas siswa pada siklus I sebesar 61,9%, sedangakan pada siklus II sebesar 74,0%. Hal ini berarti ada peningkatan aktivitas siswa dari siklus I ke siklus II sebesar 12,10%.Kata Kunci : Contextual Learning, Matematika, Aktivitas Siswa, Hasil Nilai Belajar